Pre-treatment of Nile tilapia (Oreochromis niloticus) with ozone nanobubbles improve efficacy of heat-killed Streptococcus agalactiae immersion vaccine - Nguyen Vu Linh (2022)
Nanobubble technology has shown appealing technical benefits and potential applications in aquaculture. We recently found that treatment with ozone nanobubbles (NB–O3) activated expression of several immune-related genes leading to effective response to subsequent exposure to fish pathogens. In this study, we investigated whether pre-treatment of Nile tilapia (Oreochromis niloticus) with NB-O3 can enhance specific immune responses and improve efficacy of immersion vaccination against Streptococcus agalactiae. Spleen and head kidney of fish in the vaccinated groups showed a substantial upregulation in expression levels of pro-inflammatory cytokine genes (IL-1β, TNF-α, IL-6) and immunoglobulin classes (IgM, IgD, IgT) compared with the unvaccinated control groups. The mRNA transcript of pro-inflammatory cytokine genes was greatest (approx. 2.8–3.3 folds) on day 7 post-vaccination, whereas the relative expression of immunoglobulin genes was greatest (approx. 3.2–4.1 folds) on day 21 post-immunization. Both systemic and mucosal IgM antibodies were elicited in vaccinated groups. As the result, the cumulative survival rate of the vaccinated groups was found to be higher than that of the unvaccinated groups, with a relative percent survival (RPS) ranging from 52.9 to 70.5%. However, fish in the vaccinated groups that received pre-treatment with NB-O3, bacterial antigen uptakes, expression levels of IL-1β, TNF-α, IL-6, IgM, IgD, and IgT, as well as the specific-IgM antibody levels and percent survival, were all slightly or significantly higher than that of the vaccinated group without pre-treatment with NB-O3. Taken together, our findings suggest that utilizing pre-treatment with NB-O3 may improve the immune response and efficacy of immersion vaccination in Nile tilapia.